2020
DOI: 10.3390/s20144054
|View full text |Cite
|
Sign up to set email alerts
|

Micromachined Accelerometers with Sub-µg/√Hz Noise Floor: A Review

Abstract: This paper reviews the research and development of micromachined accelerometers with a noise floor lower than 1 µg/√Hz. Firstly, the basic working principle of micromachined accelerometers is introduced. Then, different methods of reducing the noise floor of micromachined accelerometers are analyzed. Different types of micromachined accelerometers with a noise floor below 1 µg/√Hz are discussed. Such sensors can mainly be categorized into: (i) micromachined accelerometers with a low spring constant; (ii) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 115 publications
0
35
0
Order By: Relevance
“…MOEMS accelerometers combine optical measurements with the micro-electronic mechanical system (MEMS) technology. MOEMS technology has gained increasing attention in the scientific community due to its wide variety of advantages, such as immunity to electromagnetic interference, electrical insulation, corrosion resistance, remote sensing, high sensitivity, and multiplexing ability [ 2 , 3 , 4 ]. A wide range of applications exists for of this type of accelerometers, including inertial navigation with high accuracy, vibration sensing of vehicles, seismic sensing, and oil-field applications [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOEMS accelerometers combine optical measurements with the micro-electronic mechanical system (MEMS) technology. MOEMS technology has gained increasing attention in the scientific community due to its wide variety of advantages, such as immunity to electromagnetic interference, electrical insulation, corrosion resistance, remote sensing, high sensitivity, and multiplexing ability [ 2 , 3 , 4 ]. A wide range of applications exists for of this type of accelerometers, including inertial navigation with high accuracy, vibration sensing of vehicles, seismic sensing, and oil-field applications [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the previous design [ 19 ], the test results showed that the response sensitivity of the MOEMS accelerometer was about and the self-noise decreased from 185.8 ng/√Hz to 15 ng/√Hz. Among the micromachined accelerometers with sub-μg/√Hz noise floor, this type of optical accelerometer has a lower noise floor and is expected to be used in seismic surveys and other fields [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…These all have high requirements for the low-frequency performances of seismometers [ 1 , 2 , 3 , 4 , 5 ]. However, conventional seismometers based on moving-coils, optic-fibers, and piezoelectrics cannot effectively address these requirements due to poor low-frequency characteristics [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Meanwhile, electrochemical seismometers that have appeared in recent years use electrolytes as inertial masses and are featured with large working angles, high sensitivities, low noise levels, and excellent low-frequency performances.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s, micro-accelerometers were made using integrated circuits (ICs) and micromachining, which gave them the advantages of small volume [ 5 ], light weight [ 6 ], low power consumption [ 7 ], low cost [ 8 ], easy integration [ 9 ], strong overload capacity [ 10 ], and mass production [ 11 ]. These not only became the core components of micro-inertial measurement units (MIMUs) [ 12 ] but also rapidly expanded into other civil fields [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%